Opportunities for Economic Efficiency from Exporting Fruits, Vegetables and Grapes - Salamov, I.; Nazarova, M. Sh.; Djonibekov, F.; S., Kazakova Z. (European Journal of Life Safety and Stability (2660-9630), 2022)
The article presents the advantages of the use of innovative techniques and technologies in the relationship between the fruit and vegetable, viticulture sectors, changes in the activities of vegetable, fruit, viticulture, farms, including diversified farms. Profits from the sale of goods, the level of profitability of the routes, the changes in the region and districts in these sectors, the proposals that need to be implemented in the future in the field of crop and livestock, as well as a list of sources used.